How do student entrepreneurs use open innovation and incubation services to improve the performance of university-incubated startups? - Saidi, Sana; Grama‑Vigouroux, Simona; Sellami, Mohamed; Cirule, Iveta; Uvarova, Inga (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Existing knowledge regarding how student entrepreneurs leverage open innovation (OI) and incubation services within university business incubators (UBIs) to enhance the performance of university-incubated startups (UISs) is limited. We propose a model suggesting that the adoption of OI practices mediates the relationship between student entrepreneurs' OI motives and UISs’ performance, while UBI services mediate the relationship between the use OI practices and UISs’ performance. To validate our model, we conducted a quantitative survey of 97 student entrepreneurs from five UBIs in Latvia. Our findings demonstrate a dual mediating effect where the use of OI practices and UBI services significantly impacts UISs’ performance while providing valuable theoretical and practical insights.